Hidden Gem of the Cairo Consensus: Helping to End Population Growth with Entertainment Media - William Ryerson (The Journal of Population and Sustainability, 2018)
In 1994, the Programme of Action of the International Conference on Population and Development was adopted. The Programme conveys anthropocentric sensibilities when discussing the idea of sustainable development. Moreover, the Programme has largely been interpreted in such a way that it fails to hold the goal of ending population growth at the same level of esteem as the goal of ensuring reproductive health and rights. Despite some unfavorable outcomes, the Programme’s orientation around gender equality is to be celebrated. In section 11.23, the Programme highlights a key tactic to help achieve gender equality: effective use of the entertainment media, including radio and television soap operas and drama. Since 1998, Population Media Center has successfully used mission-driven entertainment to confront the most powerful drivers of ongoing rapid population growth: the social norms, attitudes and behaviors related to the status of women in various societies around the world; misinformation about contraception and cultural barriers to its use (such as male opposition); and perceived norms with regard to ideal family size.